Interannual variability of extreme precipitation in late summer over west China during 1961–2021 - Ma, Qianrong; Lei, Hongjia; Jia, Fang; Sun, Siyuan; Yan, Pengcheng; Gu, Yu; Feng, Guolin (Frontiers in Environmental Science, 2023)
The characteristics and related mechanisms of the interannual variability of late summer (August) extreme precipitation in West China (WC) were investigated from 1961 to 2021. Precipitation and extreme precipitation (defined as the 99th percentile) generally decreased in the southeast-northwest direction, with a maximum in the Sichuan Basin. The nonlinear trends in extreme precipitation have increased since the 1980s. Therefore, we further found that the interannual increase in extreme precipitation in the WC was significantly related to the eastward-strengthened South Asian high, western-stretched Western Pacific Subtropical high, enhanced westerly jet, anomalous cyclone in Mongolia, and anomalous anticyclone in the western Pacific. The anti-cyclonic anomaly is a Gill-type response to increase the sea surface temperature in the western Pacific. A mid-high latitude barotropic Rossby-wave train can be induced and has essential effects on the above key circulation patterns, further cooperating with the strong updrafts rather than strengthening and maintaining extreme precipitation in the WC.